Heritabilitas Sifat Tinggi Pohon dan Diameter Batang Shorea balangeran (Korth.) Burck di Kebun Bibit Rakyat dan Shorea leprosula Miq di Kebun Benih Semai Universitas Palangka Raya: Heitability Of Tree Height and Stem Diameter of Shorea balangeran (Korth.) Burck In Community Nurseries And Shorea leprosula Miq in Sedling Seed Orchards and Community Nurseries of The University of Palangka Raya - Sudomo, Muhammad Fadhil Amiruddin; Silvianingsih, Yosefin Ari; Pidjath, Chartina; Pindonta , Yopi Em (JURNAL HUTAN TROPIKA, 2025)
This study aims to estimate the heritability of tree height and stem diameter in two Dipterocarpaceae species, Shorea balangeran from the People’s Nursery and Shorea leprosula from the Seed Orchard of Universitas Palangka Raya. Both species play an important ecological and economic role as dominant components of peat swamp forests and lowland forests. Genetic parameters observed include genotypic variance, environmental variance, phenotypic variance, and heritability values calculated using analysis of variance (ANOVA) in a completely randomized design. The results indicate that variations in both traits are predominantly controlled by genetic rather than environmental factors. Shorea balangeran exhibited high heritability for tree height (86.18%) and stem diameter (84.25%). Likewise, Shorea leprosula showed similarly high heritability for height (85.72%) and diameter (88.53%). These high heritability values suggest that the traits are stable and heritable, making both species suitable as superior seed sources in tree improvement programs. The findings reinforce the importance of selecting plus trees to support conservation efforts and the production of high-quality seeds